Business Development Strategy for the Tofu Industry (Case Study: Pak Suharno's Business in Sidorejo Village, Curup Tengah District, Rejang Lebong Regency) - Oktoyoki, Hefri; Marina, Marina; Ansiska, Paisal; Sihasale, Daniel Anthoni (JENDELA PENGETAHUAN, 2022)
This research aims to determine the development strategy of Pak Suharno's tofu industry in Sidorejo Village, Curup Tengah District, Rejang Lebong Regency. The study was conducted from May to June 2021. The method used to determine the respondents was purposive sampling with three groups of respondents: business actors, local communities, government officials, and experts. Data analysis was performed using IFE, EFE, SWOT, and AHP matrices. The study's results indicate the presence of strengths, weaknesses, opportunities, and threats. Based on the IE (Internal-External) matrix, Pak Suharno's tofu industry in Sidorejo Village, Curup Tengah District, Rejang Lebong Regency, is in cell 5, which represents the Growth Stability or Hold and Maintain position. Alternative strategies that can be applied to Pak Suharno's tofu industry in Sidorejo Village, Curup Tengah District, Rejang Lebong Regency, are S-O (Strength-Opportunity) strategy, W-O (Weakness-Opportunities) strategy, S-T (Strength-Threat) strategy, and W-T (Weakness-Threat) strategy. Five priority hierarchies have been concluded based on the highest to lowest assessments from experts, resulting in the most attractive strategy focusing on the development of the tofu industry in Sidorejo Village, Curup Tengah District, Rejang Lebong Regency, which is to improve distribution channels (0.385). Business actors play a critical role in improving the availability of raw materials at the upstream level (0.149) and expanding distribution networks (0.047). The consideration for the SO alternative strategy (0.087) is to develop tofu products, improve marketing facilities by opening educational tourism, and collaborate with other parties to expand marketing.